Do we need better online book review organisation? (Libellarium: časopis za istraživanja u području informacijskih i srodnih znanosti, 2017)
Introduction. Online customer reviews present one of the most important factors in book purchasing or borrowing decisions. Given that only well-organized reviews are useful, Amazon has already started linking multiple formats and editions of the same book. Nevertheless, this method is not suitable for books that have appeared in many formats and editions as some attributes do not apply to all versions.Research questions. In our study we were interested in the aspects of a book users perceive as important and the extent to which these attributes match FRBR entities. We were also interested in the relation between specific attributes in the reviews and the numeric rating of the book.Methods. We used content analysis on two random samples of Amazon customer reviews. The sample included a total of 600 reviews of three well-known fiction book titles that have many formats and editions that accommodate the different preferences of readers.Results. The results show that readers take into consideration book information at various abstraction levels that match those in the FRBR model. Most reviewers comment on the book content while review readers consider reviews that comment on different aspects of a book as more helpful.Conclusions. Given that subjective opinion is an important factor in the users’ book selection decision, it would be reasonable to rethink the presentation and organisation of online book reviews.